Psychiatric-mental health education with integrated role-play and real-world contact can reduce the stigma of nursing students towards people with mental illness. (March 2021) - Gu, Libin; Jiao, Wenjuan; Xia, Haozhi; Yu, Mingming
Abstract: Stigma and negative attitudes towards people with mental illness are frequently found among nursing students. Interventions targeting mental illness stigma are the critical elements in altering the status. The aim of the present study was to examine the effects of the psychiatric-mental health education with role-play and real-world contact on stigma of nursing students towards people with mental illness in China. A single group pretest and posttest study design was adopted and total 373 students were recruited whilst 343 completed the course. We integrated the role-play and contact with patients in the routine psychiatric-mental health education. After the education was completed, the students' stigma towards people with mental illness were positively changed (pretest mean score of stigma: 53.77, posttest mean score of stigma: 49.01, 95% CI: 2.63–6.87) and their willingness to care for the people with mental illness was also significantly increased (pretest mean score of willingness: 5.45, posttest mean score of willingness: 7.38, 95% CI: −2.22–−1.65). The psychiatric-mental health education especially with integrated role-play and real-world contact is an effective way to reduce nursing students' stigma and negative attitudes towards people with mental illness and increases their willingness to care for people with mental illness. Highlights: The prominent features of the education are authentic role-play and real-world contact. Psychiatric-mental health education can reduce students' stigma towards patients. Psychiatric-mental health education can increase students' willingness in caring of patients. The comprehensive teaching method is suggested as the routine psychiatric educational strategy.